Characterization of the oral microbiome and gut microbiome of dental caries and extrinsic black stain in preschool children - Zheng, Luoyuan; Cao, Tingting; Xiong, Puling; Ma, Yulian; Wei, Limin; Wang, Jianfeng (Frontiers in Microbiology, 2023)
Introduction A lower prevalence of dental caries (hereafter termed “caries”) has been observed in children with dental extrinsic black stain (EBS). Methods We investigated the epidemiologic characterization of EBS and explored the possible role of the oral microbiome (OM) and gut microbiome (GM) in EBS formation and caries prevention. In an epidemiologic survey, 2,675 children aged 3–6 years were included. Thirty-eight of these children (7 children had both caries and EBS, 10 had EBS only, 11 had caries only, and 10 were healthy children) were recruited for 16S rRNA sequencing and collection of samples of supragingival plaque and feces. Collected plaque samples were divided into four groups: BCP (EBS+, caries+), BP (EBS+, caries−), CP (EBS−, caries+), and P (EBS−, caries−). Fecal samples were also divided into four groups: BCF (EBS+, caries+), BF (EBS+, caries−), CF (EBS−, caries+), and F (EBS−, caries−). Results EBS was observed in 12.10% of this population. Children with EBS had a significantly reduced prevalence of caries and a lower mean value of decayed–missing–filled teeth (dmft; p < 0.01). According to analyses of dental plaque, the P group had the most complex microbiome. The BCP group exhibited greater operational taxonomic unit (OTU) richness but a reduced evenness compared with the BP group, and the CP group showed greater OTU richness than the BP group. At the genus level, higher abundance of Actinomyces and Cardiobacterium species was observed in the BCP group. Higher abundance of Lautropia and Pesudopropionibacteriumin species was observed in the BP group compared with P and CP groups, respectively (p < 0.05). Veillonella species were significantly more common in P and CP groups than in BP groups, whereas Porphyromonas and Fusobacterium species were more common in the CP group (p < 0.05). With regard to the GM, the CF group exhibited greater OTU diversity than the BF group. The GM in the BCF group exhibited the most complex relationships across all fecal groups. GM groups could be distinguished by various unique biomarkers, such as Escherichia and Shigella species in the BCF group, Agathobacter and Ruminococcus species in the CF group, Lactobacillus species in the BF group, and Roseburia species in the F group. Our results suggest that EBS is a possible protective factor against early-childhood caries. Dental plaque and the GM may be relevant to EBS in primary dentition.